Implementing the proposed outer ring road in Kathmandu Valley - Shrestha, Bijaya K (Journal of Management and Development Studies, 2013)
The proposed 72 kilo meter long Outer Ring Road (ORR) project for the Kathmandu valley constitutes the construction of 50 meter wide road (eight lane highway) and development of 250 meter of land on either side through land pooling technique. It has a vision of developing the valley as a ‘national capital region’ and managing the population growth in the next 15-20 years through planned urban development. This ambitious project covers forty village development committees, three municipalities and one metropolitan city. Numerous stated objectives of the proposed ORR project such as decentralisation of commercial and office activities to the peripheral new areas through development of new ’business centres’ with mixed land use and coordinated infrastructure development at different nodal points are difficult to achieve in the present situation. The reasons are due to inadequate legal and institutional framework, poor capacity of the implementing agency, lack of master plan of the Kathmandu valley and absence of planning standards and urban design guidelines at city level. The overall results are formation of urban sprawl of residential use in the peripheral areas with traffic congestion in the existing urban centres and historic cores, acute shortage of drinking water, electricity and other basic amenities and destruction of traditional settlement in the rural areas including intensification of earthquake vulnerability. However, this mega project can be successfully implemented after improving in the existing legal and institutional framework, coordinating with the public utility providing agencies and promoting urban design approach including formulation of urban design guidelines with incentives in the form of tax cut and floor area bonus.